A Single Center Study of 1, 179 Heart Transplant Patients—Factors Affecting Pacemaker Implantation. Issue 3 (15th February 2017) - WELLMANN, PETRA; HERRMANN, FLORIAN ERNST MARTIN; HAGL, CHRISTIAN; JUCHEM, GERD
Abstract : Background: After around 10% of heart transplant patients require pacemaker implantation. The bradyarrhythmias causing pacemaker requirement include sinus node dysfunction (SND) and atrioventricular block (AVB). This study sought to define clinical predictors for pacemaker requirement as well as identify differences in the patient groups developing SND and AVB. Methods: Our operative database was used to collect retrospective recipient, donor, and operative data of all patients receiving orthotopic heart transplants between 1981 and 2016. Results: In the 35‐year period 1, 179 transplants were performed (mean recipient age 45.5 ± 0.5 years, 20.4% female, 90.6% biatrial technique) with bradyarrhythmias requiring pacemaker implantation developing in 135 patients (11.5%). Independent risk factors were prolonged operative time 340 minutes versus 313 minutes (P = 0.027) and a biatrial anastomosis (P = 0.036). Ischemia time, cardiopulmonary bypass time, aortic cross clamp time, and reperfusion time all had no significant effect on pacemaker implantation rates. Similarly, whether the transplant was a reoperation, a retransplant, or performed after primary assist implantation had no effects on pacemaker implantation rates. There was no survival difference between the paced and nonpaced groups. The donor age was higher in the patients who developed AVB as the indication for pacemaker implantation (43 vs 34 years, P = 0.031). Patients with AVB had longer aortic cross clamp times and developed the arrhythmia later than those who developed SND. Conclusions: Use of the bicaval instead of the biatrial technique and shortened operative times should reduce pacemaker requirement after heart transplantation. Survival is not affected by this complication.